2002
DOI: 10.1038/nm0502-522
|View full text |Cite
|
Sign up to set email alerts
|

Replication and compartmentalization of HIV-1 in kidney epithelium of patients with HIV-associated nephropathy

Abstract: HIV-associated nephropathy is a clinicopathologic entity that includes proteinuria, focal segmental glomerulosclerosis often of the collapsing variant, and microcystic tubulointerstitial disease. Increasing evidence supports a role for HIV-1 infection of renal epithelium in the pathogenesis of HIV-associated nephropathy. Using in situ hybridization, we previously demonstrated HIV-1 gag and nef mRNA in renal epithelial cells of patients with HIV-associated nephropathy. Here, to investigate whether renal epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
213
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(219 citation statements)
references
References 25 publications
4
213
0
1
Order By: Relevance
“…HIV-1 is strongly associated with FSGS, particularly the collapsing glomerulopathy variant, although other variants are also seen (79). The mechanisms likely involve direct infection of podocytes (80). A similar renal syndrome can be reproduced in transgenic mice bearing HIV-1 Nef (81) or Vpr (82) accessory proteins, suggesting possible mechanisms.…”
Section: Virus-associated Fsgsmentioning
confidence: 99%
“…HIV-1 is strongly associated with FSGS, particularly the collapsing glomerulopathy variant, although other variants are also seen (79). The mechanisms likely involve direct infection of podocytes (80). A similar renal syndrome can be reproduced in transgenic mice bearing HIV-1 Nef (81) or Vpr (82) accessory proteins, suggesting possible mechanisms.…”
Section: Virus-associated Fsgsmentioning
confidence: 99%
“…The pathologic variants and percentage of sclerotic glomeruli were also comparable between the two groups. These findings indicated that IgM deposition is not likely the initiation of FSGS lesion, which has been identified as several genes mutations or variants (9-13), circulating permeability factors (14)(15)(16), and others (17)(18)(19)(20)(21)(22)(23). However, IgM and complement-mediated injury may be secondary phenomena that occur after the primary renal insult.…”
Section: Discussionmentioning
confidence: 97%
“…These findings have then been confirmed by detection of HIV-1 in tubular cells as well as glomerular visceral and parietal epithelial cells by PCR amplification and RNA in situ hybridization (50). It seems that the virus is even capable of active replication and evolution within the renal epithelium (51). These findings suggest that kidney cells not only are infected with HIV-1 but also might constitute a viral reservoir, allowing the virus to undergo slow but productive replication.…”
Section: Genetic Susceptibility and Hivanmentioning
confidence: 96%